Sustainable Behavior in International Business: Corporate Social Responsibility for Mimicry or for Business Value? - Zubkova, A. B.; Makarenko, Anastasiya B.; Misiunia, Ruslan M.; Maihurova, Daria S.; Vodiakhina, Margaryta O.; Ihnatova, Anastasiia A. (ФОП Лібуркіна Л. М., 2021)
The paper is aimed at studying different pillars for the development of long-term and short-term strategies in the field of sustainable development and corporate social responsibility. The paper underlines the key differences between the concepts of sustainable development, corporate social responsibility, and ecological, social, and corporate governance. The study aims to highlight the key differences between sustainable behavior and mimicry, i.e. masking the results of companies' activity under the global or local trends in corporate social responsibility. The article focuses on studying key systems for measuring the sustainable development level. Therefore, the results of the world's leading companies have been analyzed according to the main ratings of the sustainable development level. The paper presents the empirical study of the activities of the leading Ukrainian companies in sustainable development, compares their results with those of less successful companies, examines the general situation in Ukraine. Despite the relatively high sustainable development level of the leading players in the Ukrainian market, the companies that had a lower position in the sustainability ranking got lower scores by the key components of evaluating the sustainability level. The research emphasizes the complexity of measuring the sustainable development level of enterprises, and also proposes an integrated system for evaluating the sustainable development level of enterprise, based on a combined list of components used by different analytical companies. The expediency of a more detailed monitoring of the Ukrainian companies’ activity, aiming at detecting and counteracting mimicry, is substantiated. The paper proves the necessity to develop a comprehensive measurement system for determining the sustainable development level, which will provide the most accurate evaluation and recommendations for business development.

Метою статті є дослідження різних підходів до побудови довгострокової та короткострокової стратегії в контексті сталого розвитку та корпоративної соціальної відповідальності. У статті надано огляд літератури та висвітлено відмінності між концепціями сталого розвитку, корпоративної соціальної відповідальності й екологічного, соціального та корпоративного управління. Надано структурні та характерні відмінності цих концепцій. Дослідження націлене на висвітлення ключових відмінностей між сталою поведінкою та мімікрією – маскуванням резуль татів діяльності компаній під глобальний тренд корпоративної соціальної відповідальності. Стаття фокусується на дослідженні різних систем оцінки рівня сталого розвитку. Проаналізовано результати діяльності провідних світових компаній згідно з основними рейтингами рівня ста лого розвитку. Наведено дослідження діяльності провідних українських компаній, надано порівняння з результатами менш успішних компаній, досліджено загальну ситуацію в Україні. Попри відносно високі показники рівня сталого розвитку провідних гравців українського ринку, компанії, які знаходяться нижче в рейтингу, показують низькі результати за ключовими компонентами оцінки рівня сталості. У статті наголошується на складності процесу оцінки рівня сталого розвитку підприємств, а також запропоновано інтегровану систему оцінки рівня сталого розвитку підприємства, що базується на комбінованому переліку компонентів, які використовуються різними аналітичними компаніями. Надано обґрун тування доцільності більш детального моніторингу діяльності українських компаній, з метою виявлення та протидії мімікрії, а також наголо шується на побудові комплексного алгоритму визначення рівня сталого розвитку, який надасть змогу дати якомога
Сталий розвиток в міжнародному бізнесі: корпоративна соціальна відповідальність для мімікрії чи для цінності бізнесу?
Keywords: sustainable development (SD); sustainability; sustainable development goals (SDG); corporate social responsibility (CSR); environmental; social and corporate governance (ESG); strategic management; сталий розвиток; сталість; цілі сталого розвитку; корпоративна соціальна відповідальність; екологічне, соціальне та корпоративне управління; стратегічне управління